1986
DOI: 10.1177/106002808602000202
|View full text |Cite
|
Sign up to set email alerts
|

Medical Management of Cholesterol Gallstones

Abstract: Cholesterol gallstones are a significant cause of morbidity in the U.S. Methods used to treat gallstones include cholecystectomy or medical dissolution. The primary drugs used for the dissolution of cholesterol gallstones are two bile acids, chenodeoxycholic acid and ursodeoxycholic acid. Complete or partial gallstone dissolution rates using chenodeoxycholic acid have ranged from 30 to 80 percent. Factors affecting gallstone dissolution using the bile acids include the dosage and administration schedule, obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…However, the hypothetical therapeutic use of BA in stone-forming patients would present at least two major problems: these substances are known to be (i) hepatotoxic when used at high doses (which would be necessary to yield high urinary concentrations) for prolonged periods of time; 31 and (ii) lithogenic, like other calcium sequestrant agents which cause hyperoxaluria by increasing intestinal absorption of oxalate, 32 one of the major risk factors for calcium urolithiasis. 8 In conclusion, we found that BA inhibit calcium oxalate precipitation in vitro, a property that appears of interest from both a physiopathologic and pharmacologic point of view even if does not seem currently exploitable for prophylactic or therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the hypothetical therapeutic use of BA in stone-forming patients would present at least two major problems: these substances are known to be (i) hepatotoxic when used at high doses (which would be necessary to yield high urinary concentrations) for prolonged periods of time; 31 and (ii) lithogenic, like other calcium sequestrant agents which cause hyperoxaluria by increasing intestinal absorption of oxalate, 32 one of the major risk factors for calcium urolithiasis. 8 In conclusion, we found that BA inhibit calcium oxalate precipitation in vitro, a property that appears of interest from both a physiopathologic and pharmacologic point of view even if does not seem currently exploitable for prophylactic or therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the hypothetical therapeutic use of BA in stone‐forming patients would present at least two major problems: these substances are known to be (i) hepatotoxic when used at high doses (which would be necessary to yield high urinary concentrations) for prolonged periods of time; 31 and (ii) lithogenic, like other calcium sequestrant agents which cause hyperoxaluria by increasing intestinal absorption of oxalate, 32 one of the major risk factors for calcium urolithiasis 8 …”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the size of stones was achieved in 26.3%, 33.9%, and 17.0%, respectively. In addition, reducing dietary cholesterol may improve the efficacy of bile acid therapy (1).…”
Section: Udcamentioning
confidence: 99%